Space and Gender Spaces of Difference in Canadian Women's Writing / Espaces de différence dans l'écriture canadienne au féminin - Eibl, Doris; Rosenthal, Caroline (canadiana oenipontana, 2009)
This collection of essays explores representations and constructions of space and gender in Canadian women's fiction and brings together a variety of theoretical approches, drawing on works by Nelly Arcan, Margaret Atwood, Dionne Brand, Nicole Brossard, Catherine Bush, Hiromi Goto, Anne Hébert, Marie Lafortune, Marlilú Mallet, Suzette Mayr, Tessa McWatt, Roxane Nadeau, Lilian Nattel, Gail Scott, Elise Turcotte, and Jane Urquhart. - Consacrés à la fiction canadienne au féminin, les essais réunis dans ce volume explorent des représentations et constructions spatiales en relation à la question du genre. Y sont analysées des œuvres de Nelly Arcan, Margaret Atwood, Dionne Brand, Nicole Brossard, Catherine Bush, Hiromi Goto, Anne Hébert, Marie Lafortune, Marlilú Mallet, Suzette Mayr, Tessa McWatt, Roxane Nadeau, Lilian Nattel, Gail Scott, Elise Turcotte et Jane Urquhart.